Acceleration of wound healing by composite small intestinal submucosa hydrogels through immunomodulation. (1st April 2023) - Zhang, Qing-Yi; Tan, Jie; Nie, Rong; Song, Yu-Ting; Zhou, Xing-Li; Feng, Zi-Yuan; Huang, Kai; Zou, Chen-Yu; Yuan, Qi-Juan; Zhao, Long-Mei; Zhang, Xiu-Zhen; Jiang, Yan-Lin; et al.
Abstract: Small intestinal submucosa (SIS) hydrogel is a potential candidate for wound dressing since its excellent biocompatibility and bioactivities. However, the intrinsic lack of sufficient immunomodulatory activities has limited its application. Herein, tannic acid (TA) and interleukin-10 (IL-10) were supplemented to the SIS hydrogel to fabricate a novel composite hydrogel to confer an immunomodulatory activity. In addition to the improvement in swelling and anti-degradation properties, the composite SIS hydrogel has attained satisfying free radical scavenging and sustained IL-10 release. Meanwhile, the hydrogel possessed excellent anti-oxidative and immunomodulatory abilities to promote the polarization of M2c macrophages, thereby regulating collagen synthesis and providing a favorable immune environment for angiogenesis and extracellular matrix remodeling. Above results have therefore provided a facile but effective strategy to improve the therapeutic effects of the SIS hydrogel and expand its scope of clinical applications. Graphical abstract: The composite SIS hydrogel possessed excellent anti-oxidative and immunomodulatory capacities to promote the polarization of M2c macrophages, thereby regulate collagen synthesis and provide a favorable immune environment for angiogenesis and extracellular matrix remodeling. Through these functions, the composite SIS hydrogel could effectively facilitate wound healing and attenuate scar hyperplasia. Image 1